Age-Targeted Income Taxation, Labor Supply, and Retirement - Johan Gustafsson (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper studies the life-cycle effects of favorable marginal tax treatment of older workers on their optimal life cycle labor supply, retirement timing, and savings. I develop a structural model in continuous time where the life-cycle of a representative agent is divided into three distinct phases: pre-treatment, post-treatment, and retirement. Solutions for consumption/savings, labor supply/leisure, and retirement timing are then obtained by solving the model as a salvage value problem. I then calibrate the model to Swedish earnings data and find that the increased extensive margin labor supply is partially offset by a reduction in hours worked during the pre-treatment period. The total effect is however an increase in life-cycle labor supply and consumption.
Keywords: D15; J22; J26; 330; retirement age; life cycle; tax heterogeneity; savings consumption; leisure